(untitled) (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2026)
Epilepsy represents one of the most prevalent neurological disorders globally, affecting approximately 50 million people worldwide. The classification of epilepsy and seizure types has undergone significant transformation over the past century, evolving from simple descriptive categories to sophisticated, multidimensional frameworks based on neurophysiological mechanisms. This narrative review examines the current International League Against Epilepsy (ILAE) 2017 classification system, its historical evolution, and the newly updated 2025 revisions. We explore the three-tiered diagnostic approach encompassing seizure types, epilepsy types, and epilepsy syndromes, while integrating etiological considerations throughout each level. Understanding these classification systems is essential for accurate diagnosis, appropriate treatment selection, and prognostic assessment in clinical practice.